ANALISIS FAKTOR PENYEBAB TERJADINYA KETERLAMBATAN PADA PELAKSANAAN PROYEK PEMBANGUNAN JEMBATAN - Candra Yuliana (Universitas Lambung Mangkurat, 2013)
Every construction project in general has a plan and implementation schedule that has been determined, when the implementation of the project starts, when it ends and can be completed on a predetermined time / planned. However, not all construction projects can be completed at a predetermined time. For that in this study ditelitilah factors that could cause delays on the bridge construction project case studies Batulicin Ring Bridge / South Kalimantan Province Tanah Bumbu.The method used in this research is the study of literature and data collection was done by the spread koesioner. The data were processed using nonparametric statistics using the program Statistical Product and Service Solution (SSPs) and Microsoft Excel to get the value of the Relative Rank Index (RRI) based Critical index that depends on the frequency and level of impact levels that would indicate the rank of the factors that influence in bridge construction project delays.The results showed that the most dominant factor causing delay in implementation of the project is the unpredictable weather conditions earlier, shortages of labor or personnel, equipment shortages, errors that occur during the execution of the project that must be done again, the prediction of the location of the field / geographical project , a factor late in paying wages, a complete lack of planning and the material factors that are used rarely found in the market.